Inactivated recombinant influenza vaccine: the promising direction for the next generation of influenza vaccine - Hua Shi; Ted M. Ross (Expert Review of Vaccines, 2024)
Introduction Vaccination is the most effective method to control the prevalence of seasonal influenza and the most widely used influenza vaccine is the inactivated influenza vaccine (IIV). Each season, the influenza vaccine must be updated to be most effective against current circulating variants. Therefore, developing a universal influenza vaccine (UIV) that can elicit both broad and durable protection is of the utmost importance.Area covered This review summarizes and compares the available influenza vaccines in the market and inactivation methods used for manufacturing IIVs. Then, we discuss the latest progress of the UIV development in the IIV format and the challenges to address for moving these vaccine candidates to clinical trials and commercialization. The literature search was based on the Centers for Disease Control and Prevention (CDC) and the PubMed databases.Expert opinion The unmet need for UIV is the primary aim of developing the next generation of influenza vaccines. The IIV has high antigenicity and a refined manufacturing process compared to most other formats. Developing the UIV in IIV format is a promising direction with advanced biomolecular technologies and next-generation adjuvant. It also inspires the development of universal vaccines for other infectious diseases.